Diálogos posibles en la investigación de la violencia sexual: Estándares interamericanos y el caso peruano - Mantilla Falcón, Julissa (2019)
The progress of the Interamerican Human Rights System has permitted expand the concept of sexual violence and visualize it as a violation of the human rights, in order to get legal standards to give more protection for victims. This article raises the dialogue between these inter-american standards and the Peruvian case in the period of internal armed conflict, reflected in the final report of the Commission of Truth and Reconciliation, and how this has generated an impact in the inter-american jurisprudence of human rights.